2021
DOI: 10.1111/rec.13494
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation restoration types affect soil bacterial community composition and diversity in degraded lands in subtropical of China

Abstract: Significant improvement of soil quality and biodiversity has been reported following vegetation restoration on the degraded lands in subtropical of China. However, so far the response of soil bacterial communities and drivers of their composition to differing vegetation restoration types are not well understood. In this study, we investigated soil physicochemical properties and bacterial communities in degraded land subjected to differing vegetation restoration types after 12 years of long-term experiment. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
(61 reference statements)
2
1
0
Order By: Relevance
“…Similar to the study reported by Nie et al [33] that proposed that copiotrophic microorganisms, including for example, Actinobacteria and Proteobacteria, generally increase under nutrient-rich conditions, while oligotrophic taxa, like Acidobacteria, show the opposite trend. Furthermore, RDA demonstrated that pH was the most important environmental variable driving the temporal and spatial distribution of bacteria in this paper, which is in line with previous studies [30,34]. However, we found a positive relationship between soil pH and Acidobacteria in this study, which contradicts most previous results [35], which may contribute to the inconsistent response of different Acidobacteria subgroups to changes in soil pH [36].…”
Section: Different Tea Planting Ages Shift the Soil Microbial Communi...supporting
confidence: 77%
See 1 more Smart Citation
“…Similar to the study reported by Nie et al [33] that proposed that copiotrophic microorganisms, including for example, Actinobacteria and Proteobacteria, generally increase under nutrient-rich conditions, while oligotrophic taxa, like Acidobacteria, show the opposite trend. Furthermore, RDA demonstrated that pH was the most important environmental variable driving the temporal and spatial distribution of bacteria in this paper, which is in line with previous studies [30,34]. However, we found a positive relationship between soil pH and Acidobacteria in this study, which contradicts most previous results [35], which may contribute to the inconsistent response of different Acidobacteria subgroups to changes in soil pH [36].…”
Section: Different Tea Planting Ages Shift the Soil Microbial Communi...supporting
confidence: 77%
“…However, no significant correlations were detected for the Chao1, Shannon and Simpson indices of fungi, implying that soil bacterial richness and diversity responded more sensitively to environmental changes than fungi. Additionally, numerous studies have proved that soil pH is a prevailing determinant of soil bacterial diversity in many ecosystems [29,30]. In the present study, there was a strong positive correlation between soil pH and bacterial diversity index (Shannon and Simpson), but not with the fungal diversity, which further showed that bacteria were more sensitive to environmental changes than fungi in tea plantations.…”
Section: Long-term Tea Plantation Increased Soil Bacterial Richness A...supporting
confidence: 53%
“…For improving the ecosystem functions of the “red desert,” large scale vegetation restoration, carried out by the Chinese government, was implemented and has emerged as the region's top priority. Numerous studies have reported that this initiative is a feasible approach to increasing C sequestration in both vegetation and soils (Chu et al, 2018; Yu et al, 2021; Zheng et al, 2022), but few studies have focused on the quantitative effects vegetation type has on aggregate‐associated SOC fractions and optimization configurations. In our study area, a long‐term Forest Restoration Experiment Project (FREP), was designed and executed in 1991.…”
Section: Introductionmentioning
confidence: 99%